Technical demands of different playing positions in the UEFA Champions League - Yi, Q.; Jia, H.; Liu, H.; Gómez, M. A. (International Journal of Performance Analysis in Sport, 2018)
This study aimed to identity the technical demands of different playing positions controlling the effects of situational variables in the UEFA Champions League from a long-term perspective. Data of 18 technical performance-related match actions and events achieved by 1,990 out-field players (classified into five positional roles) in 1,000 matches played in the UEFA Champions League from season 2009/2010 to 2016/2017 were collected. Generalised mixed linear modelling was employed taking the value of each of the 18 technical performance-related variables as the dependent variable, and taking the classified 5 positions as the predictor variable. Uncertainty in the true effects of the predictors was evaluated using non-clinical magnitude-based inference. Results showed that the differences between central defenders and forwards were biggest while central defenders and full backs presented the smallest difference. The performances of midfielders in variables related to passing and organising were worse than expected and wide midfielders showed relative better performances than central midfielders in passing and organising. Meanwhile, defenders, especially central defenders, achieved good performance in variables related to passing and organising. Forwards played an important role in the aspects of goal scoring and organising, they also participated in the initial defending process.